2018
DOI: 10.1063/1.5030110
|View full text |Cite
|
Sign up to set email alerts
|

Ideal form of optical plasma lenses

Abstract: The canonical form of an optical plasma lens is a parabolic density channel. This form suffers from spherical aberrations, among others. Spherical aberration is partially corrected by adding a quartic term to the radial density profile. Ideal forms which lead to perfect focusing or imaging are obtained. The fields at the focus of a strong lens are computed with high accuracy and efficiency using a combination of eikonal and full Maxwell descriptions of the radiation propagation. The calculations are performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Recently, it has been observed that by utilizing a suitable picosecond-scale pre-pulse on the surface of a plasma mirror, the scale length can be optimized [319] to minimize absorption and give reflectivities of 96% for the main pulse, Figure 39. (a) Schematic illustrating the operation principle of an ellipsoidal focusing plasma mirror to increase the intensity by a factor of five.…”
Section: Plasma Opticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been observed that by utilizing a suitable picosecond-scale pre-pulse on the surface of a plasma mirror, the scale length can be optimized [319] to minimize absorption and give reflectivities of 96% for the main pulse, Figure 39. (a) Schematic illustrating the operation principle of an ellipsoidal focusing plasma mirror to increase the intensity by a factor of five.…”
Section: Plasma Opticsmentioning
confidence: 99%
“…However, more complex gas cells with density structures, capillary discharge devices [334][335][336] and multi-pulses [337] , have been used to deliver tunable GeV-scale electron beams [230] over many centimetres of interaction length. The nonlinear plasma response can also be utilized for compressing [328] and focusing [338] short ∼30 fs beams, with expectations that they could readily handle multi-petawatt powers and deliver nearideal focusing if a suitable density profile is obtained [319] . More complex phenomena such as plasma compression and diffraction [339,340] can also be used to manipulate the beam [341] .…”
Section: Plasma Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously proposed plasma lenses in the nonblowout regime, where ponderomotive force is negligible a=w 2 Շ0:1, a transversely preformed plasma can perfectly resize the laser beam. [22][23][24][25] For absolute blowout cases Eq. (B10), the ponderomotive effect dominates and the laser beam cannot be focused by the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, w 2 is adjustable by changing d, l, and the plasma density n p . Compared to previous studies on plasma lenses for lasers, [22][23][24][25] the herein proposed concept does not require a preformed structure and is preferably suitable for petawatt class lasers.…”
Section: Introductionmentioning
confidence: 99%